Penyuluhan Inovasi Pasca Panen guna meningkatkan Nilai Ekonomi Petani Melalui Pemasaran Online - Amelia, Lenny; Rohmat, Aji (Ma'soem University, 2023)
The purpose of this activity is to take advantage of the harvest and process it into a product that can increase added value and provide income for farmers or the community by introducing online marketing. In this case, post-harvest processing is carried out through diversification of agricultural products, which are perishable food after post-harvest namely making chili sauce. The results of this activity have a positive impact on farmers and other communities, and are enthusiastic about trying and developing the knowledge gained and practiced in order to add economic value to the efficiency of a sustainable agricultural business.